2020
DOI: 10.48550/arxiv.2002.09912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Newton-Okounkov polytopes of Schubert varieties arising from cluster structures

Abstract: The theory of Newton-Okounkov bodies is a generalization of that of Newton polytopes for toric varieties, and it gives a systematic method of constructing toric degenerations of projective varieties. In this paper, we study Newton-Okounkov bodies of Schubert varieties from the theory of cluster algebras. We construct Newton-Okounkov bodies using specific valuations which generalize extended g-vectors in cluster theory, and discuss how these bodies are related to string polytopes and Nakashima-Zelevinsky polyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…In this section, we review a construction of higher rank valuations using cluster structures, following [21]. Let us start with recalling the definition of upper cluster algebras of geometric type, following [3,16] but using the notation in [14,26].…”
Section: Cluster Algebras and Higher Rank Valuationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we review a construction of higher rank valuations using cluster structures, following [21]. Let us start with recalling the definition of upper cluster algebras of geometric type, following [3,16] but using the notation in [14,26].…”
Section: Cluster Algebras and Higher Rank Valuationsmentioning
confidence: 99%
“…Gross-Hacking-Keel-Kontsevich [26] developed the theory of cluster ensembles using methods in mirror symmetry, and showed that the theory of cluster algebras can be used to construct toric degenerations of projective varieties. The author and Oya [21] gave another approach to toric degenerations by relating the theory of cluster algebras with Newton-Okounkov bodies, and constructed a family of toric degenerations of flag varieties using cluster structures. Our aim of the present paper is to prove that the toric degenerations in this family induce semitoric degenerations of Richardson varieties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(i) Gelfand-Tsetlin polytopes [33,34], (ii) Berenstein-Littelmann-Zelevinsky's string polytopes [24], (iii) Nakashima-Zelevinsky polytopes [16], (iv) Lusztig polytopes [6], (v) Feigin-Fourier-Littelmann-Vinberg (FFLV) polytopes [11,27,28], (vi) polytopes constructed from extended g-vectors in cluster theory [18],…”
Section: Introductionmentioning
confidence: 99%